ENGLISH DEPARTMENT STUDENTS’ PERCEPTIONS OF FLIPPED CLASSROOM IMPLEMENTATION IN SEMANTIC CLASS - Farida; Purwanti, Indah Tri; Eliwarti (International Journal of Educational Best Practices, 2024)
The purpose of this study was to examine the English Department students’ perceptions of flipped classroom implementation in a Semantic class at one public university in Indonesia. The data were gathered through a mixed method with questionnaires and interviews as the instruments. The researcher analysed the quantitative data using SPSS and displayed the qualitative data as supporting data. The sample for the quantitative method was 79 students from class A and B batch 2019 English Department at that university. Then, 10 students for the qualitative method were randomly from those classes. The results of quantitative data in this study showed that the English Department students at the university under investigation that university have a positive and good perception of the flipped classroom implementation in Semantics learning. In addition, the results of the qualitative data also showed positive responses that students believed the flipped classroom is an interesting method that helps them understand the materials better, increases their motivation to study, trains them to become independent learners, and improves their confidence in learning. Additionally, the flipped classroom was found to be an effective strategy in teaching and learning Semantics at the English department at one of the universities in Indonesia. Therefore, the lecturers have to consider to apply that method. Also, this method not only can be implemented in English classes but also in other courses.